University proceedings. Volga region. Social sciences - G.V. Sintsov; D.E. Feoktistov (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The article examines the constitutional and legal nature of witness immunity of Russian ombudsmen. The authors conduct a comparative analysis of constitutional legal norms and norms of procedural legislation regarding the regulation of this legal immunity. Materials and methods. To achieve the purpose of the study, the authors used formal legal and comparative legal methods. Results. Gaps and contradictions in the content of witness immunity are identified: the norms of individual procedural codes contain differ-ent rules for the application of witness immunity (Code of Criminal Procedure of the Rus-sian Federation), do not give immunity to all ombudsmen (Code of Administrative Proceed-ings of the Russian Federation) or do not contain such legal immunity at all (Code of the Russian Federation on Administrative Offenses of the Russian Federation). Positive trends in the legal regulation of witness immunity of ombudsmen have been identified: the norms of the criminal procedure code have been supplemented by rules on witness immunity of federal and regional ombudsmen; the norms of civil procedural legislation have vested im-munity in authorized persons of general and special competence. Conclusions. In addition to the need to eliminate gaps and contradictions in the regulation of witness immunities of Russian ombudsmen, the issue of waiving witness immunity on the part of the ombudsman is being discussed only with the consent of the person in whose interests the witness im-munity was granted. Key words: ombudsman, human rights commissioner, witness immun-ity, confidentiality, personal secret, professional secret.